Innovation, Sustainability and Management in Motorsports The Case of Formula E - Næss, Hans Erik (Springer Nature, 2021)
"There's probably no better sport than Formula E to present and study the science and practice of innovation within (motor)sport, and this book is a must read for those active within this fascinating area". - Dr. Kristof de Mey, Sports Technology, Innovation & Business Developer at Ghent University, Belgium This open access book provides novel insights on management innovation and sustainability in motorsport. Utilizing the all-electric racing championship called Formula E as case, it draws upon data from multiple sources such as sustainability reports of Formula and its stakeholders, media data, podcasts and newspaper articles, partner publications, and social media outputs. It aims to generate a theoretical model that describes and explains the optimal conditions for innovation when it comes to enhancing a sport organisation's commercial product. Apart from its general transferability to sports research, this model enables further study of a motorsport phenomenon that has been hailed by media as the championship, which affirms money in sustainability. It has also been emphasized by sport researchers as a highly relevant case to study management innovation. This book will be interesting to academics working in sports management, knowledge management, innovation and sustainability. Hans Erik Næss (b. 1978) is an Associate Professor in Sport Management at Kristiania University College, Norway. He holds a PhD in sociology from the University of Oslo and is the author of several peer-reviewed articles and books on motorsports, including A History of Organizational Change: The case of Fédération Internationale de l'Automobile (FIA) 1945-2020. Anne Tjønndal (b. 1988) is an Associate Professor in Sociology of Sport at Nord University, Norway. She holds a PhD in sociology from Nord University and has published articles in high-quality international journals on topics like social innovation, gender and inclusion/exclusion in sport. Tjønndal is the Celia Brackenridge International Research Award winner for 2019. ;